Optimization of Production Programs Towards a Digital Based Village - Fariah, Aen (Green Publisher Indonesia, 2020)
This research examines the optimization of the Village Profile Information System Empowerment (PRODESKEL) in Sepat Majalengka Village, towards a digital village. This research is based on the village government's vision to pursue digital village targets. Through this research, it will be illustrated to what extent is Sepat Village's readiness in pursuing the digital village targets. This study used a qualitative descriptive method, with data collection instruments in the form of interviews, questionnaires and observations from a number of primary sources in the village government. The results showed that. first, Sepat Village is a newly developing village so that the fulfillment of prodeskel-based information services is still very limited in terms of facilities, but in fulfilling the points demanded in the prodeskel program for 2020 have been maximally fulfilled. So that the village of Sepat is in a position of self-sufficiency. second, Sepat village has responded very well to the West Java governor's policy regarding digital villages, so that Sepat Village has aspirations and a direction for its development towards a digital village. It's just that the obstacles faced in getting to a digital village are still very many, most importantly the availability of human resources and infrastructure. third, the obstacles faced in the field to get to a digital village include the availability of human resources, the availability of facilities and infrastructure as well as the limited level of public awareness in the field of education